The familiar enemy: Chaucer, language, and nation in the Hundred Years War - Butterfield, Ardis (Oxford University Press, 2009)
Nation and language. Pre-nation and post-nation ; Origins and language ; A common language? -- Exchanging terms : war and peace. Fighting talk ; Exchanging terms ; Trading languages ; Lingua franca : the international language of love -- Vernacular subjects. The English subject ; Mother tongues : English and French in fifteenth-century England ; Betrayal and nation